Metasurface‐Based Abrupt Autofocusing Beam for Biomedical Applications. Issue 4 (24th February 2022) - Luo, Yuan; Tseng, Ming Lun; Vyas, Sunil; Kuo, Hsin Yu; Chu, Cheng Hung; Chen, Mu Ku; Lee, Hsiang‐Chieh; Chen, Wen‐Pin; Su, Vin‐Cent; Shi, Xu; Misawa, Hiroaki; Tsai, Din Ping; et al.
Abstract: Manipulation and precise delivery of optical energies in the regions of interest within specimens require different strategies. Hence, proper control of input beam parameters is a prerequisite. One of the prominent methods is metasurface optics, capable of crafting properties of light at nanoscales. Here, the generation of an abrupt autofocusing (AAF) beam by a nanophotonic metasurface for biomedical applications is demonstrated. Fluorescence guided laser microprofiling of mouse cardiac samples is experimentally investigated, using the AAF beam to deliver optical energy selectively to specific locations. In addition, photocoagulation of ex vivo swine skin tissue is performed and observed through optical coherence tomography. The results show great potentials for integrating metasurface optics to realize miniature laser surgery instruments for wide applications in biomedicine. Abstract : Precise delivery of optical energies by abrupt autofocusing at specific locations can be performed using a nanophotonic metasurface for biomedical applications. The advantages of an abrupt autofocusing beam are demonstrated in fluorescence guided laser micro‐profiling and photocoagulation studies. Present results show great potential for miniature laser surgery instruments for a wide range of biomedical optical instruments.